Trump’s Protectionism : What Future for US Trade Policy? - Lee, Su-Hyun (2018)
Trump’s protectionism has isolated the United States from its longstanding allies, adding uncertainty and instability to the global trading system. If a full-blown trade war erupts, the root cause can be traced back to Trump’s protectionist policy.